Improving photoreactor design with ANSYS fluent flow simulation - Coskun, Ali Canberk; Duranoglu, Dilek (PAMUKKALE UNIV, 2024)
Ansys Fluent can be used in chemical engineering to draw velocity profiles, temperature profiles inside pipes and columns and determine pressure losses, making 2D and 3D simulations of mass separation processes using user defined functions. Computational fluid dynamics (CFD) software can be applied for the analysis of photoreactors, which initiate and sustain chemical reactions through the application of light energy. Photoreactors can be used in a variety of industries and their performance can significantly impact the efficiency of the chemical processes they support. In this study, Ansys Fluent flow simulation was applied in order to improve the design of proposed photoreactor. Firstly, base photoreactor models were simulated via Ansys Fluent CFD software. Accordingly, these base models were further developed in order to obtain high fluid velocity and homogenous flow by adding baffles and nozzles. The effects of baffle height and spacing on the total velocity and flow homogeneity were also investigated. All models were analysed with the total fluid velocity on selected points and standard deviation between the velocity data. Optimal photoreactor design with the highest fluid velocity and homogenous flow distribution was developed.
Keywords: Ansys fluent; Flow simulation; Photoreactor design; BEHAVIORS; Engineering